The Impact of Facilitative Training Means on Developing the Speed and Accuracy of High Jump Shooting Performance in Handball among Kanaan Youth Forum Players - Jihad, Marwa; Saleh, Fakhri; Tawfiq, Aysin (Indonesian Journal Publisher, 2026)
The current study investigates the impact of Facilitative Training Means on enhancing the speed and accuracy of high jump shooting performance in handball among players of the Kana'an Youth Forum. An experimental design was employed due to its appropriateness for the study’s objectives. A purposive sample of (20) players was selected and randomly assigned into two equal groups: an experimental group that followed a training program incorporating Facilitative Training Means, and a control group that adhered to conventional training methods. Pre- and post-tests measuring high jump shooting speed and accuracy were conducted, and the data were analyzed using appropriate statistical procedures. The findings revealed statistically significant improvements in the experimental group’s post-test results, indicating the effectiveness of Facilitative Training Means in developing both the speed and accuracy of high jump shooting in handball.